A transboundary dilemma: dichotomous designations of Atlantic halibut status in the Northwest Atlantic. (30th March 2016) - Shackell, Nancy L.; Frank, Kenneth T.; Nye, Janet A.; den Heyer, Cornelia E.
Abstract: We investigated conflicting perspectives over a transboundary species (Atlantic Halibut- Hippoglossus hippoglossus L.) assumed to be one population spanning the border separating the USA and Canada. In Canada, the fishery is certified as sustainable by the international Marine Stewardship Council (2013). In the USA, that same population is listed as a "Species of Concern" under the US Endangered Species Act (1973). There are fishery-independent trawl surveys conducted by both USA and Canada on juvenile halibut abundance across the border. The data are sorted and both nations use their own jurisdictional boundaries to define the geographical area of their separate stock assessments. Here, we undertake a spatially unified, in-depth comparison of juvenile halibut distribution and abundance, and quantify the amount of suitable habitat for halibut across both sides of the border from 1965 to 2014. Juvenile halibut abundance was, on average, five times greater in Canada than in USA waters. The median per cent of occupied sets in Canada was about four times greater than in the US (2.5%). These differences could not be explained by the availability of "suitable" habitat. The lack of halibut in US waters, in contrast to Canada, suggests a finer-scale stock structure exists and that halibut have not re-established in the USA due to historical serial overfishing. A gradient from high occupancy of halibut in Canada to lower occupancy in the USA is evident, suggestive of connectivity between the two areas and supported by a lag correlation analysis of temporal abundance trends. The USA may now be a sink to Canada's source of halibut. While both countries have been correct in their individual assessments, a bilateral assessment of halibut would benefit both nations, and could include analyses of how fishing patterns in Canada will influence the magnitude and speed of halibut re-colonization in the USA.